2017
DOI: 10.5527/wjn.v6.i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Severe hyperkalemia following blood transfusions: Is there a link?

Abstract: Patients with gastrointestinal bleeding often require large volume blood transfusion. Among the various side effects of blood transfusion, the increase of potassium levels is a serious one which is often overlooked. We report a case of severe hyperkalemia in a patient with gastric bleeding after large volume transfusion of packed red blood cells. The patient had hyperkalemia at baseline associated with his receiving medication as well as acute renal failure following hypovolemia. The baseline hyperkalemia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…In previous reports of TAH, many patients were pediatric patients, especially neonates; 9-14 however, a significant amount of the literature reported adult patients who developed TAH. [14][15][16][17][18] Our study also shows that the age group of 1-5 years had the biggest prevalence of TAH, but seven patients were in the age group of 11 to <18 years, some of whom had an adult body size. Therefore, TAH may occur not only in the patients with a smaller body size, as we expected, but also in the patients with an adult body size.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In previous reports of TAH, many patients were pediatric patients, especially neonates; 9-14 however, a significant amount of the literature reported adult patients who developed TAH. [14][15][16][17][18] Our study also shows that the age group of 1-5 years had the biggest prevalence of TAH, but seven patients were in the age group of 11 to <18 years, some of whom had an adult body size. Therefore, TAH may occur not only in the patients with a smaller body size, as we expected, but also in the patients with an adult body size.…”
Section: Discussionsupporting
confidence: 64%
“…Serious repercussions of TAH with or without cardiac arrest have been reported, [9][10][11][12][13][14][15][16][17][18] raising concerns for the risks of TAH from large-volume transfusions with or without a rapid IR for pediatric patients, especially for infants. 19,20 Patients who are undergoing procedures such as cardiac surgeries using cardiopulmonary bypass (CPB), extracorporeal membrane oxygenation (ECMO), RBC exchange, and liver transplantations may receive large-volume RBC transfusions rapidly and may be at increased risk for TAH.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that supernatant potassium concentration of stored blood was frequently higher than potassium levels in normal human plasma, and that rapid intravenous infusion might allow a mass of potassium into receiver's body in a short time, thus swiftly increasing blood potassium concentration. [ 29 , 30 ] However, the specific mechanisms of blood transfusion inducing hyperkalemia remain unclear. Besides, surgical procedure represented another potential risk factor for hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalemia is usually associated with pediatric transfusion; it is considered a transient effect of rapid blood infusion in adults. 1,11,12 Fatal cardiac effects are the most feared consequences of hyperkalemia. The effects of hyperkalemia range from electrocardiographic changes (peaked T waves, loss of P-wave amplitude, prolonged PR interval, and QRS duration) to ventricular fibrillation or asystole, leading to mechanical arrest of the heart and death in the most severe cases.…”
mentioning
confidence: 99%
“…Hyperkalemia, or excess of potassium (K + ) in blood, is a well‐recognized adverse effect of transfusion. Hyperkalemia is usually associated with pediatric transfusion; it is considered a transient effect of rapid blood infusion in adults 1,11,12 . Fatal cardiac effects are the most feared consequences of hyperkalemia.…”
mentioning
confidence: 99%